2023
DOI: 10.12659/ajcr.941733
|View full text |Cite
|
Sign up to set email alerts
|

A 27-Year-Old Woman with an Exacerbation of Chronic Asthma Due to Influenza A Presenting with Pneumomediastinum, Retropharyngeal Emphysema, and Subcutaneous Emphysema

Abdelhadi Farouji,
Ahmad W. Haddad,
Arwa Battah
et al.

Abstract: Patient: Female, 27-year-old Final Diagnosis: Retropharyngeal emphysema • subcutaneous emphysema • pneumomediastinum Symptoms: Chest pain • shortness of breath • throat pressure Clinical Procedure: — Specialty: Critical Care Medicine • General and Internal Medicine • Pulmonology Objective: Unusual clinical course Background: Influenza infection can trigger an asthma exacerbation, which can lead to spontaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…The present study confirms that there is a positive causal relationship between lymphocyte count height and the occurrence of spontaneous pneumothorax, probably due to the fact that autoimmune and inflammatory diseases mainly invade human lymphocytes [27] , leading to the destruction of the human immune system, which results in the emergence of a variety of opportunistic lung infections and ultimately causes spontaneous pneumothorax. Bronchial asthma [28] is a common clinical condition, and its acute exacerbation is often combined with spontaneous pneumothorax, and the present study also confirms a causal relationship with the occurrence of spontaneous pneumothorax. A study at confirmed that mechanical ventilation in critically ill patients with novel coronavirus pneumonia (COVID-19) [29] had a 5.38% probability of being associated with pneumothorax, and we also confirmed that COVID was positively associated with the risk of spontaneous pneumothorax.…”
Section: Discusssupporting
confidence: 84%
“…The present study confirms that there is a positive causal relationship between lymphocyte count height and the occurrence of spontaneous pneumothorax, probably due to the fact that autoimmune and inflammatory diseases mainly invade human lymphocytes [27] , leading to the destruction of the human immune system, which results in the emergence of a variety of opportunistic lung infections and ultimately causes spontaneous pneumothorax. Bronchial asthma [28] is a common clinical condition, and its acute exacerbation is often combined with spontaneous pneumothorax, and the present study also confirms a causal relationship with the occurrence of spontaneous pneumothorax. A study at confirmed that mechanical ventilation in critically ill patients with novel coronavirus pneumonia (COVID-19) [29] had a 5.38% probability of being associated with pneumothorax, and we also confirmed that COVID was positively associated with the risk of spontaneous pneumothorax.…”
Section: Discusssupporting
confidence: 84%